Pengawasan Pengelolaan Keuangan Desa (Optimalisasi Peran BPD dan Masyarakat Dalam Mengawasi Pengelolaan Dana Desa Sekarwangi Kecamatan Cibadak Kabupaten Sukabumi) - Birkham Pahmi Safaat; Manarul Hidayat; Salsabila Putri Azzahra; Ananda Intan Fadhilah Yahya; Akmal Hidayatullah; Al Fachri Nurfath; Denisa Ramadhanty; Lala Intan Nurcahyani; Ade Armeita; Muhammad Kamil Hafidzi; Raafi Catur Wahyudianto; Daffa Satrio Wibowo; Alif Fito Dermawan; Aulia Rohman Malau; Fifi Nur Alfianti; Vella Dwi Anggraini; Betris Kristin Sosor Ambar Wati Sitorus; Bambang Rudiansah; Belva Yulivio Estiawan; Satrio Waliyudin Azhar; Firiyal Luthfi Syihab; Annisa Septi Rahayu Salsabila; Fauzi Maulana Yusuf; Anyeu Riandini; Yudi Nurahim; Fajar Wira Wardhana; Ahmad Nada; Gatot Efrianto; Arfian Arfian; Adi Utama; Heru Irianto; Rachmat Pramukty; Yusef Wandy (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
This research is motivated by the importance of supervising the use of village fund budgets, considering that there are many legal problems related to village funds involving village officials and village heads in Indonesia. Through the stages of supervision, namely monitoring, examination and evaluation and using qualitative descriptive research methods, it intends to describe the supervisory process carried out by the community in participating in supervising village funds. The result of this study is that the role of the community in participating in village fund supervision has not been optimal both from the dimensions of monitoring, examination and evaluation so it is suggested that there is a need for education or advocacy of community participation in supervising the process of using the budget and monitoring the results of village performance using village funds.